Cultural Evolution in Action: Royal Boat Song Transmission and Adaptation in Thai Buddhist Communities - Boonrod, Vich; Srisakon, Prachakon; Ruangjirayos, Purita (Resital: Jurnal Seni Pertunjukan, 2025)
This ethnographic study examines Royal Boat Song (He Ruea Luang) cultural transmission as empirical evidence for evolutionary approaches to imaginative culture. Through ethnographic fieldwork conducted in Phitsanulok Province, Thailand (2024-2025), we analyzed how this elite court tradition successfully adapted from royal water processions to community Buddhist merit-making ceremonies while maintaining core musical and ceremonial elements. Our findings demonstrate cultural transmission mechanisms predicted by evolutionary theory: selective retention of adaptive features including four-section musical structure, specialized vocal techniques, and ceremonial significance, combined with contextual modifications serving contemporary community needs through localized poetic content, Buddhist ceremonial integration, and riverbank performance venues. The research reveals how Royal Boat Songs function as adaptive cultural inheritance systems, facilitating group bonding, cultural memory preservation, and religious expression while evolving through community agency. Results show high-fidelity transmission of core musical structures with systematic adaptive variation in textual content, supporting cultural attraction theory predictions about cognitive constraints in cultural evolution. This case study provides empirical support for theories positioning imaginative culture as arising from human nature's evolved capacities for social cooperation, meaning-making, and collective identity formation, while demonstrating that cultural preservation occurs through adaptive evolution rather than static maintenance.